Design and implementation of a high strain Town rate biaxial tension test for elastomeric materials and biological soft tissue - Graham, Aaron (Department of Mechanical Engineering, 2020)
The mechanical properties of biological tissues are of increasing research interest to disciplines as varied as designers of protective equipment, medical researchers and even forensic Finite Element Analysis (FEA). The mechanical properties of biological tissue such as skin are relatively well known at low strain rates and strains, but there is a paucity of data on the high rate, high strain behaviour of skin - particularly under biaxial tension. Biaxial tensile loading mimics in vivo conditions more closely than uniaxial loading [1, 2], and is necessary in order to characterise a hyper-elastic material model[3]. Furthermore, biaxial loading allows one to detect the anisotropy of the sample without introducing noise from inter-sample variability - unlike uniaxial tensile testing. This work develops a high strain rate bulge test device capable of testing soft tissue or polymer membranes at high strain rates. The load history as well as the full field displacement data is captured via a pressure transducer and high speed 3D Digital Image Correlation (DIC). Strain rates ranging from 0.26s −1 to 827s −1 are reliably achieved and measured. Higher strain rates of up to 2500s −1 are achieved, but are poorly measured due to equipment limitations of the high speed cameras used. The strain rates achieved had some variability, but were significantly more consistent than those achieved by high rate biaxial tension tests found in the literature. In addition to control of the apex strain rate, the bi-axial strain ratio is controlled via the geometry of the specimen fixture. This allowed for strain ratios of up to 2 to be achieved at the apex 1 . When testing anisotropic membranes, the use of full field 3D DIC allowed for accurate and efficient detection of the principal axis of anisotropy in the material. No skin is tested, but instead three types of polydimethylsiloxane (PDMS, ”silicone') skin simulant are tested. These simulants were chosen to fully encapsulate the range of mechanical behaviour expected from skin - they were chosen to have stiffness's, strain hardening exponents and degrees of anisotropy significantly above or below the behaviour exhibited by skin. This ensured that the device was validated over a wider range of conditions than expected when testing skin. A novel approach to specimen fixation and speckling for silicone membranes is developed, as well as a fibre reinforced skin simulant that closely mimics the rate hardening and anisotropic behaviour of skin. In addition to bulge tests, uniaxial tensile tests are conducted on the various simulant materials in order to characterise their low strain rate behaviour. The composite skin simulant is characterised using a modified version of the anisotropic skin model developed by Weiss et al (1996) [4], and the pure silicone membranes are characterised using the Ogden hyper-elastic model.